Effects of Exercise on Sleep Quality and Insomnia in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Xie, Yi; Liu, Shuai; Chen, Xue-Jiao; Yu, Hai-Han; Yang, Yuan; Wang, Wei (Frontiers in Psychiatry, 2021)
Study Objectivies: We conducted a meta-analysis to assess the effects of different regular exercise (lasted at least 2 months on a regular basis) on self-reported and physiological sleep quality in adults. Varied exercise interventions contained traditionally physical exercise (e.g. walking, cycling) and mild-body exercise characterized by gentle exercise with coordination of body (e.g. yoga). Methods: Procedures followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Systematical searches were conducted in three electronic databases (PubMed, Embase and Web of Science) for relevant researches, which involved adult participants without pathological diseases receiving exercise intervention. Search strategy was based on the Population, Intervention, Comparison, Outcome and Study design (PICOS) framework. The self-reported outcomes included varied rating scales of Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), and Epworth Sleepiness Scale (ESS). Subgroup meta-analyses of PSQI scores were conducted based on type of exercise, duration of intervention, participants age and gender. The physiological outcomes were measured by Actigraph. All meta-analyses were performed in fixed or random statistic model using Revman software. Results: Twenty-two RCTs were included in the analysis. The overall analysis on subjective outcomes suggested that exercise interventions significantly improved sleep quality in adults compared to control interventions, with lower PSQI scores (MD -2.19; 95% CI -2.96 to -1.41), ISI scores (MD -1.52; 95% CI -2.63 to -0.41) and ESS scores (MD -2.55; 95% CI -3.32 to -1.78). Subgroup analyses of PSQI scores showed both physical and mind-body exercise interventions resulted in improvements of subjective sleep to the same extent. Interestingly, short-term interventions (≤3 months) had a significantly greater reduction in sleep disturbance versus long-term interventions (>3 months). Regarding the physiological sleep, few significant effects were found in various sleep parameters, except the increased sleep efficiency in exercise group versus control group. Conclusions: Results of this systematic review suggested that, regular physical as well as mind–body exercise primarily improved subjective sleep quality rather than physiological sleep quality in adults. Specifically, self-reported sleep quality, insomnia severity and daytime sleepiness could be improved or ameliorated with treatment of exercise, respectively evaluated by PSQI, ISI and ESS sleep rating scales.